Spontaneous fundal uterine rupture in a non-labouring 31-week twin pregnancy and unknown previous hysteroscopic adhesiolysis: A case report - Georgia Smith; Sarah Walker; Ravi Vandhana; Rebecca Swingler (Elsevier, 2021)
A 46-year-old woman presented at 31 weeks of gestation with a twin pregnancy (dichorionic, diamniotic) and with mild abdominal pain, not in labour, leading to complete spontaneous fundal uterine rupture. She underwent prompt surgical intervention and resuscitation with packed red cells, cell-salvage blood and fresh frozen plasma (FFP). Twin 1 survived and twin 2 died. Risk factors for fundal uterine rupture were multiple pregnancy and hysteroscopic adhesiolysis, which was unknown during antenatal care. The mother and twin 1 made excellent progress post-operatively. This case highlights the importance of swift intervention to minimise maternal and perinatal morbidity and mortality.